In their shoes: using fashion objects to explore the duration and complexity of wartime experiences. Issue 4 (2nd October 2021) - Bide, Bethan
ABSTRACT: Experiences of conflict rarely adhere to the historical confines of defined dates. Although the Second World War was officially brought to a close on 2 September 1945, the emotional legacy of the conflict lingered. Drawing on objects from the Museum of London, this article investigates how fashion objects can be used to highlight the long-term impacts of conflict. By looking at how people reused, saved, and fetishized wartime objects in peacetime, it shows how emotional reactions of hope, disappointment, and lingering resentment manifested themselves through practices of dressing, as well as demonstrating the uneven impact of conflict across class and gender boundaries.